Acupuncture for postprandial distress syndrome: a randomized controlled pilot trial. Issue 5 (October 2020) - Tu, Jian-Feng; Yang, Jing-Wen; Wang, Li-Qiong; Zheng, Yang; Zhang, Li-Wen; Li, Yong-Ting; Zhang, Xin; Shi, Guang-Xia; Wang, Jun; Zhao, Jing-Jie; Du, Yi; Chen, San-San; et al.
Background: Evidence for treating postprandial distress syndrome with acupuncture is limited. Aim: We aimed to evaluate the feasibility of verum acupuncture versus sham acupuncture in patients with postprandial distress syndrome. Methods: A total of 42 eligible patients were randomly allocated to either verum acupuncture or sham acupuncture groups in a 1:1 ratio. Each patient received 12 sessions over 4 weeks. The primary outcome was the response rate based on the overall treatment effect (OTE) 4 weeks after randomization. Secondary outcomes included dyspepsia symptom severity and adverse events. Results: In each group, 19 patients (91.5%) completed the study. Thirteen patients receiving verum acupuncture and seven patients receiving sham acupuncture were classified as responders according to OTE (61.9% vs 33.3%; rate difference 28.6%; p = 0.06). Dyspepsia symptom severity at the end of treatment also differed significantly between verum acupuncture and sham acupuncture groups (5.9 units vs 3.7 units; between-group difference 2.2 (95% CI, 0.2–4.2); p = 0.04). No serious adverse events occurred. Conclusion: Four weeks of acupuncture may represent a potential treatment for postprandial distress syndrome. The treatment protocol and outcome measures used in this trial were feasible. Since this was a pilot study, the efficacy of acupuncture still needs to be determined by a larger, adequately powered trial.